Literatura e mito na Escandinávia medieval: aspectos da mulher guerreira na saga de Hervor - Campos, Luciana de (2018)
Composed in thirtheenth century Iceland, the Hervör Saga, dates back to pre-Viking period of Continental Scandinavia more precisely, the year 870, in the IX century. This saga belongs to a set of literary narratives classified as "Sagas from the ancient lands of the northern lands" or Fornaldosögur, legendary sagas. This narrative will present a literary motif that has fascinated humans for centuries: the warrior woman. Studies on the myth in medieval Scandinavian literature, more precisely that of the warrior woman, which reflect in their lines a feminine condition at a certain time that is linked to the sphere of myth are still unpublished in Brazil, but in Scandinavia, and around Europe are already consolidated. With the study of the feminine condition of medieval Scandinavia represented in the sagas it is possible to propose an analysis of these female characters, more specifically that of women warriors so that one can not only understand the construction of the myth of the warrior woman, but mainly its importance both for the time when it was written and for the present. Our analysis of the myth of women warriors in literature will be based on the theory of myth proposed by authors such as Marcel Detienne and Jean-Pierre Vernant who proposes detailed analyzes of myth in literature and its repercussions on society. In the course of analyzing the myth of women warriors in literature, from Classical Antiquity to the writing of sagas in Medieval Scandinavia, we turn to literature and Scandinavian theorists who focus exclusively on the analysis of the sagas, such as Torfi Tilinius, Régis Boyer, Terry Gunnell and Margeret C. Ross, among others.